Molecular Bases for Combinatorial Treatment Strategies in Patients with KRAS Mutant Lung Adenocarcinoma and Squamous Cell Lung Carcinoma. Issue 1 (June 2016) - Lazzari, Chiara; Verlicchi, Alberto; Gkountakos, Anastasios; Pilotto, Sara; Santarpia, Mariacarmela; Chaib, Imane; Ramirez Serrano, Jose; Viteri, Santiago; Morales-Espinosa, Daniela; Dazzi, Claudio; Marinis, Filippo; Cao, Peng; et al.
Abstract Innovative therapeutic agents have significantly improved outcomes, with an acceptable safety profile, in a substantial proportion of non-small cell lung cancer (NSCLC) patients in whom the malignant phenotype of the disease is determined by oncogenic molecular alterations. However, the benefit seen with these treatment models has not translated well to NSCLCs with KRAS mutations or squamous cell histology. Although efforts have been made to develop precision medicine approaches, KRAS mutant NSCLC and lung squamous cell carcinoma (LSCC) continue to display resistance to therapy. Recently, based on the results of the Phase III SQUIRE trial, the EGFR monoclonal antibody necitumumab received FDA authorization in combination with cisplatin and gemcitabine for first line treatment of patients with metastatic LSCC. Among the molecular compounds tested in KRAS mutant NSCLC patients, the MEK inhibitor, selumentinib, combined with docetaxel in second line setting, determined a progression-free survival improvement, but no overall survival advantage. Better understanding is needed in regard to signaling pathways which cooperate to induce oncogene transformation in LSCC and KRAS mutant NSCLC and could determine intrinsic or acquired resistance to necitumumab and selumetinib. Greater understanding of such pathways will provide a molecular base upon which to improve the scant clinical benefit with these compounds.